Current African Intersections Between Intellectual Property Rights and Knowledge Access - Armstrong, Chris; Schonwetter, Tobias (My University, 2015)
In this introductory article, the two Guest Editors of this 2015 thematic issue of The African Journal of Information and Communication (AJIC) – a thematic issue focused on the theme of “African Intersections between Intellectual Property Rights and Knowledge Access” – provide practical and conceptual context for the articles and thematic reports that follow.
African Intersections between Intellectual Property Rights and Knowledge Acces
Keywords: intellectual property (IP), access to knowledge (A2K), access to medicines, Africa, openness, commons, Creative Commons, development, human rights, human security, WIPO, WTO, UNFCCC, climate change, TRIPS Agreement, Doha Declaration